Modern trends in development of elite and youth ski jumping take-off technique - Zakharov, G.G.; Belyova, A.N.; Novikova, N.B.; Adodin, N.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the dynamics of angular characteristics of take-off variations in the ski jumping of the leaders of international competitions versus the Russian elite and junior ski jumpers in the major events of 2015 through 2020. Methods and structure of the stud. The take-off techniques were side-captured at 50 fps by video camera fixed perpendicular to the jumping line opposite the take-off table edge, with the take-off technique sequence processed by StatPlusPro 7 and analyzed by DartFish Pro 10.0 software tools. Results and conclusion. The study found statistically significant (p<0.05) changes in the world bests’ take-off techniques in 2015 to 2019, particularly in the trunk angle and take-off angle; whilst the Russian elite was tested with no statistically significant progress in any of the test rates. The Russian junior ski jumpers were found to make even statistically significant regresses in the take-off angle and knee angle (p<0.05). The national ski jumping training systems, therefore, are recommended to be revised to as required by the recent take-off technique progress trends.